HYPERLACTETEMIA AND ITS TRENDS IN CRITICALLY ILL CHILDREN ADMITTED IN PEDIATRIC INTENSIVE CARE UNIT OF A DEVELOPING COUNTRY - Abbas, Qalab; Jamil, Muhammad Tariq; Khetpal, Vivek; Jafri, Leena; Haque, Anwar ul (Journal of Ayub Medical College Abbottabad, 2016)
Background: There is increasing evidence that in setting of critical ailments clinical signs lag biomarkers like Lactate and hyperlactetemia can be the only marker for this disorder. This study was conducted to describe the incidence of hyperlactatemia in critically ill children and its association with outcome. Methods: Retrospective review of medical records of all children who had their lactic acid (LA) levels measured during their admission in PICU from January 2014 to December 2015 was done. Demographic and clinical variables were recorded along with PICU therapies, outcome (Survived or expired) and development of multi-organ dysfunction. Results are presented as frequency with percentages and mean with standard deviation. Appropriate statistical tests were applied and p-value of <0.05 was taken as significant. Results: Total 300 patients had their LA measured and 202 were included in the study. Males were 130 (64%) and mean age was 5.7±4.6 years. Hyperlactatemia was found in 68 (33%) patients and another 75 (37%) had a second LA level >4 mmol/L. Increasing LA trend was found in 79 (39%) patients. Diagnostic categories included cardiovascular diseases (45, 22%), central nervous system diseases (40, 20%), respiratory diseases (31, 15%), sepsis (28, 14%), and gastrointestinal diseases14 (7%). 168 (83%) needed mechanical ventilation. Mean pH was 7.31±0.15 and metabolic acidosis was observed in 91 patients (45%). Mean LA levels in survivors and non survivors were 3.3±3.12 and 5.35±5.47 respectively. Hyperlactatemia was associated with death (p=0.01) and development of MODS (p=0.03) on univariate analysis. On multivariate logistic regression rising lactate and development of MODS were significantly associated with death (p=<0.05, odds ratio (OR) 9.24 (95% confidence interval 1.55-55.20). Conclusion: Hyperlactatemia and increasing LA trend in critically ill children are associated with worse outcome in PICU. Keywords: Hyperlactatemia; outcome, children; trend; PICU